Autologous platelets as a source of proteins for healing and tissue regeneration - Anitua, Eduardo; Andia, Isabel; Ardanza, Bruno; Nurden, Paquita; Nurden, Alan T (Thrombosis and haemostasis, 2004)
Platelets are known for their role in haemostasis where they help prevent blood loss at sites of vascular injury. To do this, they adhere, aggregate and form a procoagulant surface leading to thrombin generation and fibrin formation. Platelets also release substances that promote tissue repair and influence the reactivity of vascular and other blood cells in angiogenesis and inflammation. They contain storage pools of growth factors including PDGF, TGF-beta?and VEGF as well as cytokines including proteins such as PF4 and CD40L. Chemokines and newly synthesised active metabolites are also released. The fact that platelets secrete growth factors and active metabolites means that their applied use can have a positive influence in clinical situations requiring rapid healing and tissue regeneration. Their administration in fibrin clot or fibrin glue provides an adhesive support that can confine secretion to a chosen site. Additionally,the presentation of growth factors attached to platelets and/or fibrin may result in enhanced activity over recombinant proteins. Dental implant surgery with guided bone regeneration is one situation where an autologous platelet-rich clot clearly accelerates ossification after tooth extraction and/or around titanium implants. The end result is both marked reductions in the time required for implant stabilisation and an improved success rate. Orthopaedic surgery, muscle and/or tendon repair, reversal of skin ulcers, hole repair in eye surgery and cosmetic surgery are other situations where autologous plate-lets accelerate healing. Our aim is to review these advances and discuss the ways in which platelets may provide such unexpected beneficial therapeutic effects.